On indices and eigenvectors of quivers - Dudchenko, I.; Plakhotnyk, M. (Algebra and Discrete Mathematics, 2019)
We study formulas for eigenvectors of strongly connected simply laced quivers in terms of eigenvalues. The relation of these formulas to the isomorphism of quivers is investigated.